Airline environmental efficiency measures considering negative data: An application of a modified network Modified Slacks-based measure model. (15th September 2020) - Cui, Qiang; Jin, Zi-yin
Abstract: In this paper, we propose a new network Modified Slacks-based Measure (MSBM) model to measure environmental efficiencies of airlines when the inputs or outputs of airlines are negative. The samples are 25 global airlines from 2008 to 2018 who have negative input or output. In contrast to traditional models, this model can deal with negative data and combine the network DEA with MSBM model. Based on this, we get several important results: (1) Norwegian performs the best among these 25 airlines during 2008–2018, while Air France-KLM has the lowest overall efficiency. (2) For most airlines, their environmental efficiencies are lower than production efficiencies. (3) In order to improve the overall efficiency, airlines should take the first step to improve the efficiency of the operations stage. (4) Delta is the company with the largest increase in efficiency from 2008 to 2018. (5) The airlines in Europe perform better than the airlines of Asia, America and Oceania in all efficiencies. Highlights: We build a network Modified Slacks-based Measure model that can deal with negative data in network model. We consider two negative data: Net Profit and Greenhouse Emissions. The empirical study is done with the samples of 25 global airlines from 2008 to 2018. Norwegian performs the best among these 25 airlines.